The effect of cutting parameters on tool wear in drilling aluminium 7075 - Meera Mydin, Nur Munirah; Dahnel, Aishah Najiah; A. Raof, Natasha; Muhamad Khairussaleh, Nor Khairusshima; Mokhtar, Suhaily (TEST Engineering & Management, 2020)
Drilling is an important process for assembly operation by mechanical fasteners in automotive industry. The drilled holes must achieve a good machined surface quality requirement for part assembly. However, dry drilling of aluminium alloy 7075 is challenging due to the issues of high cutting temperature. Consequently, this can result in shorter tool life. Thus, industry overcome these issues by using coolants in the form of fluid but over the time, the fluids would be contaminated with bacteria which is harmful to the operator and could also lead to environmental issues. As to achieve a hygienic and clean process, this paper proposes to study the optimal cutting parameters in reducing tool wear when drilling aluminium 7075 in dry condition. Drilling experiments were performed using tungsten carbide drill bits at cutting speeds of 4000 to 8000 rpm and feed rates of 0.01 to 0.10 mm/rev. The tool wear was analyzed by measuring the flank of drill bits after drilling every 10 holes. The cutting speed of 4000 rpm and feed rate of 0.01 mm/rev was found to be optimal for drilling aluminium 7075 as it resulted in the least tool wear of 0.024 mm after drilling 70 holes compared to other cutting parameters. Thus, this study indicates that combination of a lower cutting speed with a lower feed rate during drilling of aluminium 7075 is beneficial to improve the life of carbide cutting tool.